The Influence of Arm Muscle Strength, Leg Muscle Explosive Power, and Arm Length on Smash Ability in Volleyball among Students at Tana Toraja State 9 High School - Charmila Charmila; Wahyuddin Wahyuddin; Fahrizal Fahrizal; Adam Adnan Mappaompo; Muh. Adnan Hudain (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The primary aim of this research is to investigate the impact of arm muscle strength, leg explosive power, and arm length on the effectiveness of a smash in volleyball games. The study will be conducted among participants in extracurricular activities at SMA Negeri 9 Tana Toraja. Materials and methods. In this study, the population under consideration consisted of all extracurricular students at SMA Negeri 9 Tana Toraja. The research sample size comprised 20 individuals. The data was analyzed using descriptive analysis and path analysis methods, and the analysis was conducted with the assistance of the SPSS version 25 computer program. The significance level chosen for the study was 95%, denoted by α = 0.05. Results. The study's findings are as follows; 1) There is a correlation between arm muscle strength and smash ability in volleyball extracurricular activities for students at SMA Negeri 9 Tana Toraja, with a 70.7% correlation, 2) There is a correlation between leg muscle explosive power and smash ability in volleyball extracurricular activities for students at SMA Negeri 9 Tana Toraja, with a 72.9% correlation, 3) There is a correlation between arm length and smash ability in volleyball extracurricular activities for students at SMA Negeri 9 Tana Toraja, with an 83.1% correlation, 4) There is a correlation between arm muscle strength, arm length, and smash ability in volleyball extracurricular activities for students at SMA Negeri 9 Tana Toraja, with an 81.3% correlation. Conclusion. In volleyball extracurricular activities for SMA Negeri 9 Tana Toraja students, there is a significant influence of leg muscle explosive power and arm length on smash ability. The study yielded a 66.7% result, indicating the importance of these physical attributes in enhancing performance on the volleyball court.